1989
DOI: 10.2307/1938120
|View full text |Cite
|
Sign up to set email alerts
|

Retention and Transport of Nutrients in a Third-Order Stream in Northwestern California: Hyporheic Processes

Abstract: Chloride and nitrate were coinjected into the surface waters of a third-order stream for 20 d to examine solute retention, and the fate of nitrate during subsurface transport. A series of wells (shallow pits) 0.5-10 m from the adjacent channel were sampled to estimate the lateral interflow of water. Two subsurface return flows beneath the wetted channel were also examined. The conservative tracer (chloride) was hydrologically transported to all wells. Stream water was > 88% of flow in wells < 4 m from the wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
401
3
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 522 publications
(419 citation statements)
references
References 44 publications
14
401
3
1
Order By: Relevance
“…[2] The hyporheic zone is the area of the streambed and banks where water from the active channel mixes with sediment pore water and returns to the channel [Triska et al, 1989;White, 1993;Harvey and Wagner, 2000;Gooseff, 2010]. Channel bed morphologies, such as steps, pools, and riffles, intensify the vertical flux of water through the hyporheic zone by a variety of hydraulic mechanisms [Elliott and Brooks, 1997;Hester and Doyle, 2008;Buffington and Tonina, 2009;Tonina and Buffington, 2009;Endreny et al, 2011a].…”
Section: Introductionmentioning
confidence: 99%
“…[2] The hyporheic zone is the area of the streambed and banks where water from the active channel mixes with sediment pore water and returns to the channel [Triska et al, 1989;White, 1993;Harvey and Wagner, 2000;Gooseff, 2010]. Channel bed morphologies, such as steps, pools, and riffles, intensify the vertical flux of water through the hyporheic zone by a variety of hydraulic mechanisms [Elliott and Brooks, 1997;Hester and Doyle, 2008;Buffington and Tonina, 2009;Tonina and Buffington, 2009;Endreny et al, 2011a].…”
Section: Introductionmentioning
confidence: 99%
“…Hyporheic flow is the exchange of groundwater and stream water across the stream bed and banks (Triska et al, 1989). Hyporheic zones are temporally and spatially dynamic (Harvey and Wagner, 2000) and many researchers have investigated hyporheic exchange because of its influence on the biogeochemical and ecological functioning of stream ecosystems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This area of research has expanded as N loading to terrestrial and aquatic ecosystems has increased (Vitousek et al 1997;Turner and Rabalais 2003), and concerns over deleterious impacts on receiving water bodies have grown (Rabalais et al 2009). Stream reach nutrient export is impacted by both biological (i.e., uptake) and physical (i.e., hydrologic loss) retention (Triska et al 1989;Hart et al 1992;Covino et al 2010), and research has shown that in-stream uptake (i.e., biological retention) can be strongly influenced by nutrient concentration (Dodds et al 2002;Earl et al 2006;O'Brien et al 2007). The relationship between biological uptake and nutrient concentration is of particular concern because nutrient uptake efficiency has been shown to decrease with elevated concentrations (Mulholland et al 2002).…”
mentioning
confidence: 99%